1992
DOI: 10.2989/02577619209504707
|View full text |Cite
|
Sign up to set email alerts
|

The 1980s – a decade of change in the Benguela ecosystem

Abstract: Changes that occurred in sea surface and some deeper temperatures, surface winds, currents, plankton and some dominant crustacean (rock lobster Jasus lalandii), molluscan (squid Loligo vulgaris reynaudii and abalone Haliotis midae), fish (anchovy Engraulis capensis, pilchard Sardinops oce/latus, Cape hakes Merluccius spp., sole Austroglossus pectoralis, kingklip Genypterus capensis and various species of linefish) and seabird (Cape gannet Morus capensis) resources in the Benguela ecosystem in the 1980s are doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…if the amount of density-dependence was affected by extrinsic forces with population crashes occurring when poor conditions occurred at high densities , there has been a sustained decrease across all three Namibian populations (at a rate of 10% per annum at the smallest colony) despite low densities. All five west coast Cape gannet colonies are dependent on the highly productive Benguela upwelling ecosystem (Shannon et al 1992). However, the contrasting fortunes of the three Namibian and two South African colonies accord with strong regional differences in the health of fish stocks in this oceanographic system.…”
Section: Discussionmentioning
confidence: 99%
“…if the amount of density-dependence was affected by extrinsic forces with population crashes occurring when poor conditions occurred at high densities , there has been a sustained decrease across all three Namibian populations (at a rate of 10% per annum at the smallest colony) despite low densities. All five west coast Cape gannet colonies are dependent on the highly productive Benguela upwelling ecosystem (Shannon et al 1992). However, the contrasting fortunes of the three Namibian and two South African colonies accord with strong regional differences in the health of fish stocks in this oceanographic system.…”
Section: Discussionmentioning
confidence: 99%
“…Mills 1995). The increase in jellyfish abundance in the northern Benguela appears to have coincided with a period of declining pelagic fish catches there (Shannon et al 1992, FAO 1995, and it has been suggested that these phenomena are directly linked. Although the diets of C. hysoscella and A. aequorea are not well described, related species are known to prey upon fish eggs and larvae (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the two systems provides a framework for developing a more comprehensive view of the factors that influence the sensitivity of biological production to wind forcing and for a better understanding of the underlying dynamics of EBUS ecosystems in general . This can also be useful for predicting the response of EBUS to potential wind changes induced by climate change (Bakun, 1990;Shannon et al, 1992;Mendelssohn, 2002;McGregor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%